On the modal functions of Lithuanian verbs of coming - Jasionytė-Mikučionienė, Erika (Kalbotyra, 2017)
The verbs of coming and going as a means of modality have been investigated in a number of languages: Russian (Majsak 2005; Bourdin 2014), Latvian (Wälchli 1996, 2000), Estonian (Penjam 2006), Finnish (Kangasniemi 1992) and others. However, with the exception of some observations made by Wälchli (1996) or Nau (2012), the realization of modality by ‘come’ or ‘go’ verbs in Lithuanian has not been thoroughly examined. Thus, the present paper is concerned with a diachronic as well as synchronic variation pertaining to two Lithuanian verbs of motion that contain the root ‘go’, i.e. pareiti ‘come home, return’ and prieiti ‘approach on foot’ as well as their reflexive counterparts. The article seeks to establish to what extent the verbs under analysis have developed modal meanings in Contemporary Lithuanian as well as the earliest period of the language (16th–17th centuries) and to account for the possible diachronic evolution of modal meanings. It focuses on both qualitative as well as quantitative parameters. The data have been collected from the old written Lithuanian texts (16th–17th centuries) and the corpus of the Contemporary Lithuanian Language, namely its subcorpus of fiction texts. The text sample on which the study is based shows that the modal constructions with the Lithuanian verbs of motion based on the root ‘go’ appear in the 16th century. It is only the reflexive forms pareitis(i) (‘PREF-go-REFL’) and prieitis(i) (‘PREF-go-REFL’) that have potential to realise non-epistemic modality: the analysed material did not reveal any instances where non-reflexive forms pareiti and prieiti are used to convey modality. The predominant modal meaning of the reflexive verbs pareitis(i) and prieitis(i) concerns the meaning of participant-external as well as deontic necessity. As for Contemporary Lithuanian, the ‘go’-derived necessive constructions are rather marginal in the contemporary system of modality: the verbs under analysis are more common in spoken Lithuanian or dialects than in written Lithuanian. Moreover, semantic distribution among the reflexive verbs under consideration differs in Old and in Contemporary Lithuanian. Deontic necessity takes the leading position among the reflexive verb pareitis(i) in Old Lithuanian, whereas participant-external necessity predominates among the reflexive verb prisieiti in Contemporary Lithuanian.
Keywords: verbs of coming; participant-external necessity; modal and non-modal meanings; necessive constructions; old Lithuanian texts; corpus-based analysis